Improving Students' Ability in Expressing Criticism for Text Response Through the Application of Problem Based Learning - Dedi (Journal of Islamicate Studies, 2022)
The background of the problems addressed include: (1) Students' understanding of the material being taught; especially on differentiating exemplum texts, critical responses are still low; (2) The ability of students to solve problems in Indonesian language learning is not optimal; And (3) active participation of students in learning is still weak. According to the problem, the effort to fix it is through: (1) Learning improvement activities with Collaborative Classroom Action Research (PTKK) 2 (two) cycles of Indonesian subjects; (2) Implementing innovative, creative, effective, and interesting learning by using the Problem Based Learning (PBL) learning model; and (3) carry out learning activities. Differentiating exemplum texts, critical responses by applying the expository method; question and answer; work in group; observation; discussion The results of CAR activities in Indonesian subjects can be stated to be carried out with the procedures and activity steps in 2 (two) cycles well. This is proven, among others: (1) almost all of the students or 94.74% obtained scores above the KKM (75) with an average value (Cognitive Mean of students) of 83.95; (2) Skill level of students according to KD almost entirely or 98.68% of students skilled in basic competencies. Differentiating exemplum texts, critical responses with very good qualifications. And (3) the level of active participation of students in learning reached 91.534% which was declared very high..